Mixtures of organic and inorganic substrates, particle size and proportion. - Morales-Maldonado, Emilio Raymundo (2015)
The objective of this paper was to review the mixtures of organic and inorganic materials used in the preparation of a new material, particle size, proportion, and their response in plant. In Mexico, agricultural waste is considered as a pollutant reservoir; however, from another perspective, this represents an industry with great potential. The nutrients ingested by animals represent nutriments available for plants when properly recycled. An option that minimizes the risk of contamination and improves its quality is the production of compost and vermicompost. Both processes are an alternative to organic production. A material by itself does not meet the optimum conditions. Reducing the volume of an organic material increases compaction and compression of roots, affecting the efficiency of irrigation and fertilization, so it is necessary to make mixtures with inorganic materials, that is used in the development of a new material for better growing conditions of the plant.